DIABETES DIET SELF-MANAGEMENT OF PEOPLE WITH TYPE 2 DIABETES MELLITUS IN JEMBER REGENCY, EAST JAVA PROVINCE, INDONESIA: OVERVIEW - Rondhianto Rondhianto (UPT Penerbitan Universitas Jember, 2022)
Diabetes diet self-management is an important component in type 2 diabetes mellitus (T2DM) management to improve diabetes outcomes, reduce the risk of complications and disability, improve quality of life, and prevent premature death. The purpose of this study was to describe diabetes diet self-management among people with T2DM. The research method is descriptive-analytic with a cross-sectional design. The subjects were people with T2DM in Jember Regency. The sample size is 180 respondents with multistage random sampling. The instrument is Self-Management Dietary Behaviors Questionnaire. Data were analyzed by descriptive and inferential analysis (Kruskal-Wallis test and Mann-Whitney U test). The results showed that the average age of the respondents was 55.33 ± 6.98 years. The majority of respondents are women (67.8%), married (83.9%), basic education (46.1%), low income level (66.1%), and Madurese (51.7%). The majority of respondents had the ability to self-manage a diabetic diet in the moderate category (61.7%), with an average score of 42.89±9.063. There are differences in the self-management of diabetes diet based on education level, income level, and ethnicity (p=0.002; p=0.004; p=0.001 < =0.05). Meanwhile, based on age, gender, and marital status there was no significant difference (p=0.706; p=0.168; and p=0.217 > =0.05). Interventions for self-management of diabetes diet in people with T2DM should pay attention to sociodemographic conditions, especially education level, income, and ethnicity to improve adherence and diabetes outcomes. Keywords: type 2 diabetes mellitus, self-managament, diet diabetes